Nationalism and Women in Croatia - Gjurgjan, Ljiljana Ina (Array, 1992)
The article juxtaposes the traditional feminist concept that privileges the gender and the nationalist one which sees the nationalist affiliation as the dominant factor of identity creation. Discussing the case of the recent war atrocities in Croatia, the paper argues that the question of national vs. gender affiliation is never that simple and loyalties are always divided.